Coupled Effect of Water Temperature and Cyclic Wetting and Drying on Dynamic Mechanical Characteristics of Sandstone - Pu Yuan; Ning-Ning Wei; Qin-Yong Ma; Ju-Cai Chang (Advances in Civil Engineering)
Considering the periodical moisture variation in deep rock masses, cyclic wetting and drying under high geothermal condition is a vital issue for the safety and stability of deep rock engineering. To investigate the coupled effect of water temperature and cyclic wetting and drying on dynamic mechanical characteristics of sandstone, dynamic uniaxial compressive tests were carried out under the same loading condition for sandstone specimens subjected to cyclic wetting and drying treatment. When the temperature was 60°C in both wetting and drying processes, cyclic wetting and drying treatment presents a detrimental effect on the tested sandstone. Both physical and dynamic uniaxial compressive characteristics deteriorate in an exponential function with the increase of wetting and drying cycles. Based on SEM image analyses, the initiation and propagation of microcracks is mainly the result of cyclic loading and unloading of tensile stresses induced by water absorption and desorption of kaolinite within sandstone during cyclic wetting and drying treatment. After 15 cycles of wetting and drying, the deterioration of both physical and dynamic uniaxial compressive characteristics first increase then decrease with water temperature in wetting process elevating from 20°C to 98°C. SEM images indicate that more microcracks generate when water temperatures increase from 20°C to 60°C, while the micromorphology is changed and fewer microcracks display due to kaolinite mobilization when water temperature increases from 60°C to 98°C. The threshold value for the effect of water temperature on cyclic wetting and drying is found to be about 60°C for the tested sandstone.